Impact of angiopoietin-2 on kidney diseases - Li, Mei; Popovic, Zoran V.; Chu, Chang; Reichetzeder, Christoph; Pommer, Wolfgang; Krämer, Bernhard; Hocher, Berthold (Kidney diseases, 2023)
Background: Angiopoietins (Ang) are essential angiogenic factors involved in angiogenesis, vascular maturation, and inflammation. The most studied angiopoietins, angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2), behave antagonistically to each other in vivo to sustain vascular endothelium homeostasis. While Ang-1 typically acts as the endothelium-protective mediator, its context-dependent antagonist Ang-2 can promote endothelium permeability and vascular destabilization, hence contributing to a poor outcome in vascular diseases via endothelial injury, vascular dysfunction, and microinflammation. The pathogenesis of kidney diseases is associated with endothelial dysfunction and chronic inflammation in renal diseases. Summary: Several preclinical studies report overexpression of Ang-2 in renal tissues of certain kidney disease models; additionally, clinical studies show increased levels of circulating Ang-2 in the course of chronic kidney disease, implying that Ang-2 may serve as a useful biomarker in these patients. However, the exact mechanisms of Ang-2 action in renal diseases remain unclear. Key Messages: We summarized the recent findings on Ang-2 in kidney diseases, including preclinical studies and clinical studies, aiming to provide a systematic understanding of the role of Ang-2 in these diseases.
Online veröffentlicht: 14. März 2023
Gesehen am 30.09.2024